Identification of Key Residues for Interaction of Vasoactive Intestinal Peptide with Human VPAC1 and VPAC2Receptors and Development of a Highly Selective VPAC1Receptor Agonist - Pascal Nicole; Laurence Lins; Christiane Rouyer‐Fessard; Cyrille Drouot; Pierre Fulcrand; A. G. Thomas; Alain Couvineau; Jean Martínez; Robert Brasseur; Marc Laburthe (2000)
The widespread neuropeptide vasoactive intestinal peptide (VIP) has two receptors VPAC1 and VPAC2. Solid-phase syntheses of VIP analogs in which each amino acid has been changed to alanine (Ala scan) or glycine was achieved and each analog was tested for: (i) three-dimensional structure by ab initio molecular modeling; (ii) ability to inhibit 125I-VIP binding (Ki) and to stimulate adenylyl cyclase activity (EC50) in membranes from cell clones stably expressing human recombinant VPAC1or VPAC2 receptor. The data show that substituting residues at 14 positions out of 28 in VIP resulted in a >10-fold increase of Ki or EC50 at the VPAC1receptor. Modeling of the three-dimensional structure of native VIP (central α-helice from Val5 to Asn24 with random coiled N and C terminus) and analogs shows that substitutions of His1, Val5, Arg14, Lys15, Lys21, Leu23, and Ile26 decreased biological activity without altering the predicted structure, supporting that those residues directly interact with VPAC1 receptor. The interaction of the analogs with human VPAC2 receptor is similar to that observed with VPAC1 receptor, with three remarkable exceptions: substitution of Thr11 and Asn28 by alanine increased Ki for binding to VPAC2receptor; substitution of Tyr22 by alanine increased EC50 for stimulating adenylyl cyclase activity through interaction with the VPAC2 receptor. By combining 3 mutations at positions 11, 22, and 28, we developed the [Ala11,22,28]VIP analog which constitutes the first highly selective (>1,000-fold) human VPAC1 receptor agonist derived from VIP ever described.